2010
DOI: 10.1038/jp.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between one and three doses a week of recombinant erythropoietin in very low birth weight infants

Abstract: Objective: To compare transfusion requirements and erythropoietic response in preterms between schedules of rEPO administration once or three times per week, using the same weekly dose.Study Design: Prospective, randomized trial including infants weighing <1500 g at birth and/or were p32 weeks' gestation: Group 1 (60 infants) received subcutaneous rEPO at 250 units kg À1 per dose, three times weekly for 6 weeks; Group 2 (59 infants), at 750 units kg À1 per dose, once weekly for 6 weeks. Efficacy was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Higher erythropoietic activity with the thrice-weekly dosing regimen has also been reported in previous studies. 5,6 There was no significant difference in ferritin level between the groups, similar to other reports. 5,6 In comparing the 2 dosing regimen, our study showed that EPO dosing of 750 IU/kg once-weekly was inferior to EPO 250 IU/kg thrice-Fig.…”
Section: A Comparison Of Once-and Thrice-weekly Erythropoietin Dosing...supporting
confidence: 90%
See 1 more Smart Citation
“…Higher erythropoietic activity with the thrice-weekly dosing regimen has also been reported in previous studies. 5,6 There was no significant difference in ferritin level between the groups, similar to other reports. 5,6 In comparing the 2 dosing regimen, our study showed that EPO dosing of 750 IU/kg once-weekly was inferior to EPO 250 IU/kg thrice-Fig.…”
Section: A Comparison Of Once-and Thrice-weekly Erythropoietin Dosing...supporting
confidence: 90%
“…There were several recent studies reporting comparable effectiveness between once-and thrice-weekly EPO dosing with no significant differences in the frequency of adverse events. 5,6 Simplification of the dosing regimen is attractive and may help improve in the compliance with therapy with the reduction in the number of injections, therefore reducing the frequency of pain inflicted, and decreased hospital revisits, staff workload and risk of medication errors. Aiming towards service improvement, we studied whether once-weekly dosing of EPO was comparable to thrice-weekly dosing in treating AOP.…”
Section: A Comparison Of Once-and Thrice-weekly Erythropoietin Dosing...mentioning
confidence: 99%
“…Male preterm infants have a higher risk of abnormal neurological outcome than female preterm infants,41 and more boys in the current study might have influenced the incidence of neurological disability and the effects of rhEPO treatment. Fourth, a subsequent follow‐up for 5 years42 or until the children start school43 might further help determine whether early administration of rhEPO to very preterm infants improves neurodevelopmental outcomes.rhEPO was originally used at a low dose to prevent anemia in preterm infants, and it is now widely accepted as a routine application for all preterm infants as a substitute for blood transfusion, although the dose, duration, and route of rhEPO administration has been modified and is different from its original usage 23, 25, 44. Animal experiments showed that high‐dose rhEPO (10,000–30,000U/kg) decreases both short‐term and long‐term brain injury, but it must be given at the time of, or very soon after, brain injury 12, 45.…”
Section: Discussionmentioning
confidence: 99%
“…Polycythemia, rash, seizures, hypertension, shortened time to death, myocardial infarction, congestive heart failure, progression of tumors, and cerebrovascular accident have been reported in adults. 4,5 We report the first case of dermal erythropoiesis as a side effect of rEpo in an extremely premature born infant presenting with late-onset blueberry muffin lesions. 2,3 None of these effects have been noted in the neonates.…”
mentioning
confidence: 97%